Nitric oxide and fibrinogen in patients with subclinical hypothyroidism and their possible relation to cardiovascular damage (International Journal of Medical and Surgical Sciences, 2021)
Endothelial dysfunction as well as hypercoagulability have been described as the initial triggers of atherosclerosis and cardiovascular damage and have been associated with subclinical hypothyroidism (SHC). The aim of this research was to determine the concentration of nitric oxide (NO), fibrinogen and circulating lipids in patients with subclinical hypothyroidism and to correlate these variables with thyrotropin (TSH) concentration to establish their possible association with the development of cardiovascular damage. A descriptive, cross-sectional, correlational study was conducted at the IESS Hospital in Riobamba, Ecuador, in the period from January 2019 to September 2021. Ninety-five subjects were studied (65 patients with CAH and 30 controls). The concentration of total cholesterol, triglycerides, HDL cholesterol and LDL cholesterol, TSH, free thyroxine, ON and fibrinogen were determined. Results: We found a decrease in the concentration of ON (p
Keywords: cardiovascular damage; subclinical hypothyroidism; nitric oxide; fibrinogen; tsh